(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
A number of communities, most of which have distinctive long-established knowledge and know-how base, populate Kerala state. Indigenous technological knowledge can be encouraged through a scientific approach as one of the means of sustainable agricultural practices, which will be environment-friendly. ITK that are in practice all over rural India is little acknowledged and there is a threat of loss of this knowledge. Hence some of the local knowledge and technologies were studied and the importance of the same has been evaluated. The study was carried out within the scaffold of poultry farming and allied activities. A broad range of varied sectors including poultry housing, feeding and disease management were taken into account for the purpose of the study. It is observed from the study that farmers adopt traditional knowledge in every aspects of poultry farming including housing, brooding, feeding management, hatching process, seasonal management, poultry health management etc. The documented ITKs showed the richness of the time-tested traditional knowledge applied to animal husbandry in the region specified under the study.